QUATERNARY GEOLOGY OF PORTIONS OF THE MCGREGOR PEAK, MURR PEAK, MARION, AND HUBBART RESERVOIR, 7.5’ QUADRANGLES, FLATHEAD COUNTY, MONTANA - Montejo, Carlos (Digital Commons @ Montana Tech, 2021)
Quaternary deposits in the northern Little Bitterroot River watershed record the advance and retreat of the Cordilleran Ice Sheet, transgression of Glacial Lake Missoula, and at least one partial or complete drainage of Glacial Lake Missoula during the last Pleistocene glaciation. New geologic mapping at a scale of 1:24,000 in portions of the McGregor Peak, Marion, Murr Peak, and Hubbart Reservoir quadrangles with a focus on Quaternary deposits has refined boundaries for where the Cordilleran Ice Sheet and Glacial Lake Missoula coincided. Stratigraphic analysis of three measured sections within Glacial Lake Missoula sediments along with three optically stimulated luminescence ages on quartz grains in sands below and within the glaciolacustrine sediments constrains the age of initial lake transgression to between 21.8 ± 1.4 and 20.3 ± 1.2 ka. These ages are consistent with regional chronological data within and outside of the lake basin. Unlike other studies on the stratigraphy of Glacial Lake Missoula sediments, stratigraphic sections in this study area do not show conclusive evidence of regression and subaerial exposure such as desiccation cracks and periglacial modification. A fan-shaped deposit containing boulders with long dimensions > 5 m at the mouth of a steep canyon along the Little Bitterroot River is evidence of high-velocity flows which produced bedrock scours that were subsequently filled to form lakes. These features are interpreted to record at least one glacial outburst flood after Glacial Lake Missoula had reached its maximum elevation.